Meta-Analysis of Integrated Therapeutic Methods in Noninvasive Lower Back Pain Therapy (LBP): The Role of Interdisciplinary Functional Diagnostics - Aleksandra Bitenc-Jasiejko; Krzysztof Konior; Danuta Lietz-Kijak (Pain Research and Management)
Introduction. Lower back pain (LBP) is almost a problem of civilizations. Quite often, it is a consequence of many years of disturbed distribution of tension within the human body caused by local conditions (injuries, hernias, stenoses, spondylolisthesis, cancer, etc.), global factors (postural defects, structural integration disorders, lifestyle, type of activity, etc.), or systemic diseases (connective tissue, inflammation, tumours, abdominal aneurysm, and kidney diseases, including urolithiasis, endometriosis, and prostatitis). Therefore, LBP rehabilitation requires the use of integrated therapeutic methods, combining the competences of interdisciplinary teams, both in the process of diagnosis and treatment. Aim of the Study. Given the above, the authors of the article conducted meta-analysis of the literature in terms of integrated therapeutic methods, indicating the techniques focused on a holistic approach to the patient. The aim of the article is to provide the reader with comprehensive knowledge about treating LBP using noninterventional methods. Material and Methods. An extensive search for the materials was conducted online using PubMed, the Cochrane database, and Embase. The most common noninterventional methods have been described, as well as the most relevantly updated and previously referenced treatment of LBP. The authors also proposed noninvasive (measurable) diagnostic procedures for the functional assessment of the musculoskeletal system, including initial, systematic, and cross-sectional control. All figures and images have been prepared by the authors and are their property. Results. This review article goes beyond combining a detailed description of each procedure with full references, as well as a comprehensive discussion of this very complex and troublesome problem. Conclusions. Lower back pain is a serious health problem, and this review article will help educate physicians and physiotherapists dealing with LBP in the options of evidence-based treatment. Ultimately, the article introduces and postulates the need to systematize therapeutic procedures in LBP therapy, with a long-term perspective.